Analisis Kritis Etika Politik Kasih Tinjauan Fratelli Tutti 154 Perang Melawan Politik Individualisme - Aliano, Yohanes Alfrid; Welan, Yeremia Anton Julianus; Lau, Stefanus; Arianto, Josep (Jayapangus Press, 2023)
This study discusses the phenomenon of the